Effects of angiotensin and vasopressin V-1 receptors on water and sodium intake induced by injection of vasopressin into lateral septal area - Mima, EGO; Andrade, R. R.; Camargo, LAA; Saad, W. A. (Elsevier B.V., 2004)
The specific arginine(8)-vasopressin (AVP) V, receptors antagonist (AAVP) was injected (20, 40 and 80 nmol) into the lateral septal area (LSA) to determine the effects of selective septal V, receptor on water and 3% sodium intake in rats. Was also observed the effects of losartan and CGP42112A (select ligands of the AT(1) and AT(2) ANG II receptors, respectively) injected into LSA prior AVP on the same appetites. Twenty-four hours before the experiments, the rats were deprived of water. The volume of drug solution injected was 0.5 mul. Water and sodium intake were measured at 0.25, 0.5, 1.0 and 2,0 h. Injection of AVP reduced the water and sodium ingestion vs. control (0.15 M saline). Pre-treatment with AAVP (40, 80 and 160 nmol) did not alter the decrease in the water ingestion induced by AVP, whereas AAVP abolished the action of AVP-induced sodium intake. Losartan (40, 80 and 160 nmol) did not alter the effect of AVP on water and sodium intake, whereas CGP42112A (20, 40 and 60 nmol) at the first 30 min increased water ingestion. Losartan and CGP42112A together increased the actions of AVP, showing more pronounced effects than when the two antagonists were injected alone. The results showed that AVP inhibited the appetites and these effects were increased by the AAVP. The involvement of angiotensinergic receptors in the effects of AVP is also suggested. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: AVP; AAVP; AT(1) receptor; AT(2) receptor; water intake; sodium intake